Editorial: Tropical Montane Forests in a Changing Environment - Salinas, N.; Cosio, E.G.; Silman, M.; Meir, P.; Nottingham, A.T.; Román Cuesta, Rosa María; Malhi, Y. (Frontiers Media, 2021)
Tropical montane forests (TMFs) are found on most of Earth's continents along variable elevation ranges, whose potential upper limits are influenced by cloud condensation heights and minimum temperatures. They are most widespread in South America and in (semi-)humid mountain areas.